Biologics in Microangiopathic Wounds. (December 2018) - Papi, Massimo; Papi, Claudia
In the last decades the possibility to diagnose a skin ulcer has greatly improved. We learnt that a consistent percentage of nonhealing ulcers may be caused by a microangiopathic disorder that has not been properly investigated and cured. Pathogenetically, we can distinguish 2 main groups: (1) ulcers due to inflammatory microangiopathy, mainly including cutaneous small and medium vessel vasculitis, pyoderma gangrenosum, and connective tissue diseases, and (2) ulcers due to occlusive microangiopathy. The group of microangiopathic occlusive ulcers is more heterogeneous and includes different disorders ranging from livedo vasculopathy to calciphylaxis, hydroxyurea-induced ulcers, antiphospholipid antibodies ulcers, and various other types. These conditions can induce thromboses or anatomo-functional occlusion of cutaneous microvessels. Despite different physiopathologic mechanisms, the ulcer resulting from a primitive microangiopathy may receive basic treatments that are in the complex similar to other pathogenetically different wounds, including MOIST-based local therapy and elastic compression when it is not contraindicated. Persistent inflammatory processes are increasingly demonstrated as responsible for the chronicity of many skin ulcers. New data concerning the biological phases of wound healing and the molecules that play crucial roles in this process suggested the use of new specific therapies. Some of them such as growth factors and platelet-rich plasma are prevalently used as topical biologic agents with variable benefits. In recent years, a new class of systemic anti-inflammatory molecules, better known as biologic drugs, have been introduced in the cure of chronic inflammatory diseases that can induce microangiopathic injuries and ulcerative complication. They enlarged the therapeutic options in case of nonresponder microangiopathic ulcers and could represent a future model of "pathogenetically based" therapy of skin ulcers.